Study of Perinatal Outcomes in Multifetal Gestation on the Basis of Chorionicity. (Med Phoenix, 2022)
Introduction: Multiple pregnancy is simultaneous development of more than one fetus in uterus. Multifetal gestations are found to be associated with significantly higher maternal morbidity and associated health care service costs. Women with multifetal gestation are nearly six times more likely to be hospitalized with complications, including preterm labor, preeclampsia, preterm premature rupture of membrane, placental abruption, hydramnios and postpartum haemorrhage. The term multifetal gestation includes twins, triplets and high order multiples.Objectives: To evaluate maternal and neonatal complications and pregnancy outcomes of multifetal gestation on the basis of chorionicity.Materials and Methods: This was a hospital based cross-sectional study conducted at tertiary care hospital for a period of one year from August 2020 to September 2021. A total of 58 twin pregnancies and 2 triplet pregnancies with meeting the inclusion criteria were enrolled in the study after taking consent.Results: The most common maternal complication among twin pregnancy was preterm delivery (41.37%). Other maternal complication was premature rupture of membrane (32.75%), primary postpartum haemorrhage (24.13%), anemia (8.62%), Pregnancy induced hypertension (8.62%), Preeclampsia (8.62%), Placental Abruption (5.10%). Most common neonatal complication was low birth weight (63.79%). Among the two-triplet pregnancy both were Trichorionic Triamniotic with preterm delivery via lower segment caesarean section at 32 weeks. Both of these triplet pregnancies had IUGR babies.Conclusion: Multifetal gestation is a high-risk pregnancy associated with adverse maternal and fetal outcomes. Early diagnosis of chorionicity and proper follow up throughout the gestation improves the perinatal outcome.